2012
DOI: 10.1016/j.dyepig.2011.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Switching azonaphthols containing a side chain with limited flexibility. Part 1. Synthesis and tautomeric properties

Abstract: A series of azo dyes, possessing amide fragments with restricted flexibility tethered to 4-(phenyldiazenyl)naphthalen-1-ol, was obtained from 1-hydroxy-2-naphthoic acid by subsequent conversion to amides and diazo coupling. It was shown that the position of the tautomeric equilibrium in solution strongly depends on the solvent in both UV and NMR concentration scale. The compounds exist as pure enol forms in chloroform and hydrocarbons, while in polar solvents (acetone, acetonitrile, alcohols) a tautomeric mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Unfortunately, the efficiency of the switching system crucially depends on tautomerism in the parent skeleton: it works in the case of the azonaphthols 13 and 14 [14] and the heterocyle 15 [15], but does not in azophenol 16 or azoanthranol 17, where the tautomeric equilibrium is strongly shifted a priori. The replacement of the side arm, as it is in 18 [16] and 19 [17], does not stabilize the enol tautomer because of keto dimer formation (18) or double hydrogen bonding stabilization of the keto tautomer (19). …”
Section: Causes Of Reversal In Tautomeric Form: Selective Stabilizatimentioning
confidence: 99%
“…Unfortunately, the efficiency of the switching system crucially depends on tautomerism in the parent skeleton: it works in the case of the azonaphthols 13 and 14 [14] and the heterocyle 15 [15], but does not in azophenol 16 or azoanthranol 17, where the tautomeric equilibrium is strongly shifted a priori. The replacement of the side arm, as it is in 18 [16] and 19 [17], does not stabilize the enol tautomer because of keto dimer formation (18) or double hydrogen bonding stabilization of the keto tautomer (19). …”
Section: Causes Of Reversal In Tautomeric Form: Selective Stabilizatimentioning
confidence: 99%
“…Several theoretical and experimental studies on the azo-hydrazone tautomeric equilibrium can be found in the literature. However, due to the dependence of the tautomeric forms on the surrounding chemical environment, their structural and spectroscopic characterizations are not trivial. Indeed, many issues concerning the relative stability of these species and related with the intramolecular proton transfer that interconvert them into each other remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the formation of the seven-membered hydrogen-bonding ring in 6E cannot compete with the flexibility of the system in the case of the intermolecular association. Compared to another tautomeric C=O containing ionophore, recently developed [13], it seems that the existence of a carbonyl group leads in some cases to stabilization of the keto tautomer through formation of associates.…”
Section: Resultsmentioning
confidence: 99%